2014
DOI: 10.1002/14651858.cd008567.pub3
|View full text |Cite
|
Sign up to set email alerts
|

General physical health advice for people with serious mental illness

Abstract: Background There is currently much focus on provision of general physical health advice to people with serious mental illness and there has been increasing pressure for services to take responsibility for providing this. Objectives To review the effects of general physical healthcare advice for people with serious mental illness. Search methods We searched the Cochrane Schizophrenia Group's Trials Register (last update search October 2012) which is based on regular searches of CINAHL, BIOSIS, AMED, EMBASE, Pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 63 publications
1
42
0
Order By: Relevance
“…Three recent systematic reviews have investigated physical illness as a co-morbid condition for those who experience severe mental illness (Tosh et al 2011, Hardy et al 2011, Happell et al 2012a) From these reviews key areas for consideration in the physical and mental health care delivery emerged, placing mental health nurses in an ideal position to monitor the adverse physical impact of pharmacotherapy, assess service patients' physical health needs and promote a change in lifestyle choices to enhance physical wellbeing (Howard & Gamble 2011, Happell et al 2012c). Gray et al (2009) asked if the mental health nurse does not intervene to improve the physical health needs of mental health patients who will?…”
Section: Assessment and Managing Physical Health Needs In Mental Healmentioning
confidence: 99%
“…Three recent systematic reviews have investigated physical illness as a co-morbid condition for those who experience severe mental illness (Tosh et al 2011, Hardy et al 2011, Happell et al 2012a) From these reviews key areas for consideration in the physical and mental health care delivery emerged, placing mental health nurses in an ideal position to monitor the adverse physical impact of pharmacotherapy, assess service patients' physical health needs and promote a change in lifestyle choices to enhance physical wellbeing (Howard & Gamble 2011, Happell et al 2012c). Gray et al (2009) asked if the mental health nurse does not intervene to improve the physical health needs of mental health patients who will?…”
Section: Assessment and Managing Physical Health Needs In Mental Healmentioning
confidence: 99%
“…Recovery focused care that encourages the person to lead a productive life with meaning, hope and purpose beyond the effects of mental illness (Slade 2010) is also firmly embedded in these policy statements (Australian Health Ministers 2009;Department of Health 2011;Mental Health Commission of Canada 2012). However, as a group, people with a mental illness still face many obstacles in their recovery journey that include the high rate of physical health co-morbidities and mortality (Park et al 2011;Shuel et al 2010;Stanley & Laugharne 2012;Tosh et al 2011;Tranter et al 2012;Vanderlip et al 2014;Viron et al 2014;Weiser et al 2009;). They are likely to have at least one chronic medical condition and to develop that illness at a younger age than the general population (Bezyak et al 2011;El-Mallakh et al 2010;Galon & Graor 2012;Viron & Stern 2010;Wiley-Exley et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review has demonstrated the importance of physical health advice on physical health awareness and physical health behaviours in people with mental illness (Tosch et al, 2011). A recent 6-month randomized controlled trial has also highlighted the importance of long-term lifestyle strategies for weight gain management in the people with schizophrenia (Attux et al, 2013).…”
Section: Discussionmentioning
confidence: 99%